Anomalous Anterior Papillary Muscle as an Autopsy Finding in Two Cases1. Issue 2 (12th March 2013) - Strajina, Veljko; Živković, Vladimir; Nikolić, Slobodan
Abstract Anomaly in the anterior papillary muscle (APM) is known to cause left ventricle outflow tract (LVOT) obstruction, and this rare congenital condition could be a cause of sudden cardiac death. This anomaly and its hemodynamic effects is similar to valvular heart disease. In our two described cases, in which cause of death was, respectively, hypertrophic cardiomyopathy and suicide by hanging, the cephalad portion of the left APM was inserted directly into the ventricular surface of the anterior mitral leaflet and chordae tendineae were absent in the area of the direct anomalous muscle insertion; the aberrant papillary muscle was very large and showed an exaggerated anterior displacement within the left ventricular cavity. The described anomaly is a cause of LVOT obstruction. This condition is considered to be rare, although incidence estimates do not exist. In the absence of other possible causes, this finding may indicate arrhythmia as being the immediate cause of death.